Revitalizing business tourism in the European Union : strategies for growth - Carvalho, Pedro (2023)
The COVID-19 pandemic had a disastrous effect on the growth in business tourism, emphasizing the role of information and communication technologies in the implementation of new meeting models. Consequently, new needs and concerns of the business tourist may have arisen, which should lead business tourism organizations to consider new attributes in their value proposition. Thus, this study aims to understand the determinants of business tourism spending and the number of business meetings, in the European Union, to aid the formulation of economic and marketing policies, in the post-pandemic period. For this purpose, a literature review is carried out for the periods before, during, and after the pandemic phase; additionally, a panel data analysis is performed using data from the 28 countries in the European Union. The results identify new typologies of determinants, describing first-order (global-scale) and second-order (European-scale) determinants and identifying important practical implications.